Evaluating the role of Smartpilot® view assisted target-controlled infusion anesthesia during intracranial mass surgery: A comparative retrospective study with bispectral index-guided standard anesthesia - İnan, Gözde and Emmez, Gökçen and Pampal, Kutluk and Özköse Şatırlar, Zerrin (Journal of Surgery and Medicine, 2021)
Background/Aim: Neuroanesthesia necessitates the control of both systemic and cerebral hemodynamics, the prevention of intracranial pressure increase, knowledge of anesthetics’ cerebral effects, and early neurological recovery. The titration of anesthetics becomes crucial to optimize the appropriate level of anesthesia required for surgery while reducing postoperative neurological consequences. Smartpilot® View (SPV) is a new decision support system that uses pharmacologic models to optimize anesthetic depth and improve patient outcomes. The goal of this study was to compare the effectiveness of SPV with standard BIS-guided anesthesia administration in terms of intraoperative hemodynamic stabilization, anesthetic consumption, and postoperative recovery times during intracranial mass surgery. Methods: Following ethics committee approval, the records of the patients who underwent elective supratentorial craniotomy between November 15, 2017 and March 15, 2018 were reviewed retrospectively. The demographics of the patients, anesthesia and surgery times, eye opening and extubation times, time to reach an Aldrete score of 9 and anesthetic consumptions were compared between those who were monitored with SPV in addition to BIS (SPV Group) and those who were monitored with solely BIS for standard anesthetic follow-up (BIS Group). Results: A total of 139 subjects were analyzed (SPV (n=71), BIS (n=68)). Hemodynamic responses to induction and intubation were more pronounced in the BIS group (P<0.05). Time until eye opening and extubation were 3.6 (2.4) versus 6.06 (1.63) minutes and 5.76 (1.3) versus 9.16 (1.0) minutes in the SPV and BIS groups (P<0.001). In the SPV Group, it took much less time to achieve an Aldrete score of 9 or above (P<0.001). Total consumed amount of both propofol and remifentanil were significantly lower in the SPV group (P<0.001). Conclusion: Use of SPV compared to BIS-guided routine anesthesia follow-up improved titration and consumption of anesthetic drugs, thereby facilitating the early recovery process in patients who underwent intracranial mass surgery.